Effect of subsurface irrigation on the productivity and technological quality of sugarcane - Filho, Joao Alberto Fischer [UNESP] (2022)
The aim of the study was to evaluate the effect of irrigation depths, via subsurface drip, on the technological quality, productivity, and water use efficiency (WUE) of sugarcane cultivars. The experimental design was of balanced blocks with 12 blocks and two factors: cultivars (CTC 4, IACSP93-3046, RB86-7515, IACSP95-5000 and IAC91-1099) and irrigation depths (dry, deficit and supplementary). From the estimated evapotranspiration (ETc), irrigation depths equivalent to 100% of crop ETc were defined for the supplemental treatment and 50% for deficit. The amounts of sucrose in the juice (POL) and the cane (PC) did not differ among the cultivars; however, additional irrigation provided higher values of the evaluated parameters. The purity levels of all treatments were superior to those recommended (85%) and differed between the cultivars. In the supplementary irrigation regime, the IAC91-1099 cultivar had the highest total recoverable sugar value (TRS), equal to 165.62 kg Mg-1, and the highest yields of stalks and sugars, 157.02 and 26.01 Mg ha-1, respectively. The WUE was superior in the dry regime for the CTC4 and RB86-7515 cultivars, and these were considered tolerant to the water deficit. The deficit irrigation provided average gains in the yield of sugarcane and sugar similar to supplementary irrigation; consequently, there were substantial reductions in water use and irrigation requirements in addition to energy savings.